ANALISIS PENGARUH STRATEGI BISNIS ONLINE (E-COMMERCE) DALAM MENINGKATKAN MINAT BELI KONSUMEN - Rosyidah Rachman; Rizna Gelbi Permata Hati (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
This study aims to analyze online bussiness strategies (e-commerce) in increasing consumer buying interest. This research was conducted at the Orin Babok Online Shop. The type of research used is associative research. The data used is quantitative data with primary data sources. Data collection is done by the questionnaire method. Data were analyzed using simple linear regression analysis technique, t test and coefficient of determination test (R2). The results showed that the online bussiness strategy (e-commerce) had a positive and significant effect on consumer buying interest at the Orin Babok Online Shop. A positive relationship means that if the online marketing strategy (e-commerce) increases, the consumer's buying interest will also increase. This is indicated by the value of the calculated coefficient of tcount which is greater than the value of ttable (18,767 > 2,011). The results of the coefficient of determination test (R2) obtained the value of Adjusted R Square is 0.878. This means that the magnitude of the influence of online bussiness strategy variables (e-commerce) on consumer buying interest at Orin Babok Online Shop is 87.8%, while the remaining 12.2% is caused by other variables beyond the scope of this study, such as product quality, prices, discounts and others.